(untitled) (Revista Archai, 2023)
The two most compelling accounts of the friend in Plato’s Lysis are that the neither good nor bad is friend of the good and that the akin is friend of the akin. In this paper I challenge a common interpretation that these accounts are the same, similar to, or compatible with one another. I argue instead that the two accounts are incompatible because they rely on opposing assumptions about the nature of desire and its relationship to need and about friendship and its orientation towards what benefits the one who loves. Although I do not offer a comprehensive interpretation of the dialogue, I argue that, given his main assumptions about the friendship, desire, and philosophy in the Lysis, Socrates could only endorse first of these accounts, that the neither good nor bad is a friend of the good, if indeed endorses any of them.